Dynamics of spillover network among oil and leading Asian oil trading countries' stock markets. (15th September 2020) - Ashfaq, Saleha; Tang, Yong; Maqbool, Rashid
Abstract: Asia as the largest continent which has the highest consumption of energy, so analyzing the impact of spillover and energy crisis is crucial for this region. In this article the volatility spillovers connections among crude oil, leading Asian oil-exporting and oil-importing countries' stock exchanges are scrutinized. This study applies the VAR-DCC-GARCH model to examine the spillover network structure with the nine years of daily data from September 01, 2009 to August 31, 2018. The results of these analyses have been displayed the network connections using complex networking technique. Overall strong spillover relations were found among oil-exporting as well as with oil prices. The strong interconnection is alarming for these economies, it is recommended to diversify their dependence on other sectors of the economy too. On the other side, oil-importing countries documented low as well as fewer interconnections and also with oil prices. It means these economies are more self-dependent, they also need to make long term planning to deal with future crisis shocks. Further, the findings of this study will provide an insight to researchers and policymakers regarding the spillover networking among oil and leading Asian trading countries' stock markets. The networking of the oil price spillover can be extended for the Asian oil trade and subsequent to the whole world. Highlights: Highlights volatility spillovers connections among crude oil, leading Asian oil trading countries' stock exchanges. Applies the VAR-DCC-GARCH model to examine the spillover network structure. Displayed the network connections using complex networking technique. Showed strong spillover relations among oil-exporting as well as with oil prices.